Assessment of Nurses' Practices Towards Children with Diabetic ketoacidosis - Rami Hassen Hussen Allawi, Mahmoud Mohammad Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess of nurses' Practices towards children with diabetic ketoacidosis. Methods: A descriptive study design was used to achieved the objectives of the study. The study was conducted in four government hospitals includes: Ibn AI-Atheer Teaching Hospital, Al-Khansaa Teaching Hospital, Mosul General Hospital and AL-Salam Teaching Hospital. The non-probability (purposive) sampling method was selected for the study comprised of (30) Nurses from the pediatric departments (ward, intensive care units) of Mosul hospitals. The data was analysis by descriptive statistics in SPSS version 24 by using frequency, percentage Results: The study showed that the 53% (16) of the nurses were aged range from 25 to 29 year in the study, The demographic information showed that the majority of the staffs in the study group were male 57% (17). Most of the participants are married people 70% (21), most of the them had a bachelor's degree 67% (20). In related to general year of experience the study found that most of nurses 63% (16) have (1-5) years of experience and finally the study found that 43% (13) of nurses have 1 year work duration in pediatric department. Conclusion: The researchers concluded that nurses' practices towards caring for patients with DKA were poor in all aspects, which increases the risk of disability and mortality among them. Keywords: Assessment, Practices , Diabetic ketoacidosis